(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The article describes the features of mountain lifestyle associated with more complex and difficult survival conditions compared to other areas. Mountain dwellers face challenges such as harsh climatic conditions, low agricultural productivity, higher logistical and energy costs of life support, communication isolation and lack or weak links to markets, limited access to social and economic services. These factors make economic activity in mountains particularly difficult and risky, generating poverty, social conflicts and political instability. A proposal was made for the socio-economic stabilization of situation in mountainous countries, by writing off and exchanging external debt for sustainable mountain development.